1995
DOI: 10.3109/00365529509093305
|View full text |Cite
|
Sign up to set email alerts
|

Indomethacin-Induced Lesion Modifies Contractile Activity in Rat Small Intestines

Abstract: The results suggest that treatment of the rat with indomethacin enhances contractility of the small intestine owing to diminution of acetylcholinesterase activity independently of the degree of lesions and reduces it owing to decreased responsiveness of enteric neurons with the progression of lesions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
8
0

Year Published

1995
1995
2011
2011

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 20 publications
2
8
0
Order By: Relevance
“…Furthermore, although there was no significant correlation between transit time and overall RIS, there appeared to be an association between primary (non-consequential) late effects and delayed transit. Our results are in agreement with those of Lu and coworkers [54], who reported that motility changed independently of the degree of severity of mucosal injury in a rat model of indomethacin-induced lesions. These findings are compatible with a mechanism mediated through neurohumoral pathways, rather than by anatomical presence of an injured segment of bowel.…”
Section: Discussionsupporting
confidence: 83%
“…Furthermore, although there was no significant correlation between transit time and overall RIS, there appeared to be an association between primary (non-consequential) late effects and delayed transit. Our results are in agreement with those of Lu and coworkers [54], who reported that motility changed independently of the degree of severity of mucosal injury in a rat model of indomethacin-induced lesions. These findings are compatible with a mechanism mediated through neurohumoral pathways, rather than by anatomical presence of an injured segment of bowel.…”
Section: Discussionsupporting
confidence: 83%
“…The application of atropine failed to significantly modify the contractile response to 5-HT in the adult rat small intestine. This observation correlates with previous studies demonstrating that the contractile response to 5-HT was insensitive to antagonism by atropine in the isolated rat ileum and colon [9] . In comparison, pretreatment of the neonatal rat ileum with atropine significantly reduced contractile responses induced by 5-HT, suggesting that the 5-HT-induced contractions are at least partially cholinergically mediated.…”
Section: Discussionsupporting
confidence: 81%
“…Fioramonti and Bueno (10) reported that decreased amplitude of spike potentials and abolished fasting migrating motor complexes were shown in indomethacin-induced gastric damage. In addition, Lu et al (20) demonstrated that after indomethacin administration, intestinal segments with lesions failed to produce peristaltic activity, whereas in those segments with no visible lesions the peristaltic activity was enhanced. Concerning gastric emptying of Sustacal ® , we were not able to find any difference between control and indomethacin-treated animals, at any time point or doses utilized.…”
Section: Discussionmentioning
confidence: 99%